Electronic supply network coordination in intelligent and dynamic environments : modeling and implementation - Mahdavi, Iraj, 1962-; Mohebbi, Shima, 1984-; Cho, Namjae (Hershey, PA : Business Science Reference, 2011)
'This book presents cutting-edge knowledge on scientific approaches to the management of supply networks in a highly informed global environment with abundant dynamic and uncertain challenges'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Business logistics; Inventory control; Materials management; Information technology -- Management